Effect of meteorological parameters and air pollutants association with health risk assessment during the pandemic in Delhi, India - Bhupendra Pratap Singh; Kriti Mehra; Khyati Chowdhary; Charvi Khanna; Sandeep Gautam; Seema Chahal; Jamson Masih; Jyotsana Gupta (Discover Public Health)
Abstract The outbreak of the novel Coronavirus disease (COVID-19) in December 2019 in Wuhan, China, rapidly spread across the globe, impacting over 210 countries, including India. The nationwide lockdown in 2020 significantly improved air quality due to the suspension of transport, industrial, and construction activities. This study evaluates the variations in PM₂.₅ and PM₁₀ concentrations across multiple monitoring stations in Delhi, India, from 2019 to 2021, along with the influence of meteorological parameters and associated health risks. The mean concentrations of PM₂.₅ and PM₁₀ were 109.54 µg/m³ and 214.04 µg/m³, respectively, for the study period. Year-wise analysis revealed average PM₂.₅ levels of 113.33 µg/m³ (2019), 108.92 µg/m³ (2020), and 106.92 µg/m³ (2021), while PM₁₀ levels were 221.34 µg/m³, 203.02 µg/m³, and 220.04 µg/m³, respectively. A substantial reduction in PM₂.₅ was observed during the lockdown, attributed to restricted anthropogenic activities. Strong positive correlations were found for PM₂.₅ and PM₁₀ among Alipur, ITO, Okhla, Narela, and Wazirpur stations. Meteorological analysis indicated a negative correlation between PM concentrations and temperature, wind speed, and solar radiation, whereas moisture and wind direction showed a positive relationship. The health risk assessment, based on Hazard Quotient (HQ) values, indicated that children and infants were more vulnerable to adverse health effects than adults, particularly in the pre- and post-pandemic periods. These findings emphasize the role of emission control strategies in improving air quality and mitigating health risks.